Variability and genetic merits of white Guinea yam landraces in Nigeria - Agre, A.P.; Edemodu, A.; Obidiegwu, J.; Adebola, P.O.; Asiedu, R.; Asfaw, A. (Frontiers Media, 2023)
Introduction: Landraces represent a significant gene pool of African cultivated white Guinea yam diversity. They could, therefore, serve as a potential donor of important traits such as resilience to stresses as well as food quality attributes that may be useful in modern yam breeding. This study assessed the pattern of genetic variability, quantitative trait loci (QTLs), alleles, and genetic merits of landraces, which could be exploited in breeding for more sustainable yam production in Africa.